Blockchain and AI technology in the industrial Internet of things - Pani, Subhendu Kumar 1980-; Lau, Sian Lun 1976-; Liu, Xingcheng 1964- (IGI Global, 2021)
"With blockchain technology and artificial intelligence fueling the concept and growth of the Industrial Internet of Things, this book investigates the intersection of information science, computer science, and electronics engineering as it ushers in a new era for industrial and manufacturing companies"--
"Premier Reference Source" -- taken from front cover. - Includes bibliographical references and index. - Description based on title screen (IGI Global, viewed 05/08/2021)
Keywords: Blockchains (Databases); fast; Internet of things; fast; Electronic books; Blockchains (Databases); Internet of things